Pencegahan Diabetes Mellitus Berbasis Inovasi “Bujuk Ke ABB” pada Masyarakat Desa Awang Bangkal Barat Kecamatan Karang Intan - Agianto, Agianto; Darmayanti, Yuniar Darmayanti; Lamattapa, Muhammad Adam; Susanti, Susanti; Noviana, Rena; Atni, Desty Kartika; Alisa, Alisa (Progran Studi Farmasi Universitas Mandala Waluya, 2024)
ABSTRACT The wetland environment plays an important role in human life, but also has the potential to cause disease, including diabetes mellitus. Data shows that the prevalence of diabetes is still high in Awang Bangkal Barat Village, which is caused by a lack of public awareness of the importance of maintaining a healthy lifestyle and having regular health checks. Community service activities in Awang Bangkal Barat Village are carried out to provide health education to all levels of society. Collaboration with the village and Karang Intan 2 Community Health Center was carried out to maximize this activity. The results of the questionnaire showed that activity participants had increased knowledge and motivation regarding the prevention and control of diabetes mellitus. Activities are carried out in two directions and provide the community with the opportunity to ask questions so that the level of community knowledge improves. Keywords: Diabetes Mellitus, Prevention of Diabetes Mellitus, Health Education, Inovation